Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1253/circj.cj-09-0378
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Growth Hormone-Releasing Peptide on Myocardial Oxidative Stress and Left Ventricular Dysfunction in Dilated Cardiomyopathic Hamsters

Abstract: Background: Growth hormone-releasing peptide (GHRP) may act directly on the myocardium and improve left ventricular (LV) function, suggesting a potential new approach to the treatment of cardiomyopathic hearts. The present study tested the hypothesis that the beneficial cardiac effects of GHRP might include attenuation of myocardial oxidative stress. Methods and Results:Dilated cardiomyopathic TO-2 hamsters were injected with GHRP-2 (1 mg/kg) or saline from 6 to 12 weeks of age. F1B hamsters served as controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…Here, we found that GH effectively decreased ROS levels in GC. Our result is consistent with the antioxidant effects of GH in other types of cells including vascular endothelial cells, myocardial cells and skeletal muscle cells [14][15][16] , suggesting an important mechanism that GH improves oocyte quality.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here, we found that GH effectively decreased ROS levels in GC. Our result is consistent with the antioxidant effects of GH in other types of cells including vascular endothelial cells, myocardial cells and skeletal muscle cells [14][15][16] , suggesting an important mechanism that GH improves oocyte quality.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, Weall et al [13] reported that GH improved the expression of GHR, the mitochondrial function and fertilization rate of oocytes in older women. GH can function reduce OS in some types of cells [14][15][16]. However, the ability of GH to improve OS in patients with POR has not been assessed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Administration of angiotensin II receptor blockers (ARB), 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (statins), vitamin C, β-blockers, allopurinol and growth hormone-releasing peptide reduces oxidative stress and improves cardiac and vascular function in CHF. [19][20][21][22][23] Furthermore, exercise training decreases oxidative stress in CHF. 24 We have reported that 2 weeks of Waon therapy decreased urinary concentrations of 8-epi-PGF2α, a marker of oxidative stress, in patients with at least one atherosclerotic risk factor.…”
Section: Effect Of Waon Therapy On Oxidative Stress In Chfmentioning
confidence: 99%
“…Oxidation of phospholipids in the fatty acid membranes results in the generation of several highly toxic lipid peroxidation products such as 4-hydroxy- trans -2-nonenal (HNE) and acrolein (Porter et al 1995; Niki 2009). Increased levels of HNE or HNE-modified protein adducts have been detected in the hearts of dilated cardiomyopathic hamsters (Kato et al 2010), hypertensive rats (Benderdour et al 2003; Benderdour et al 2004), rats infused with isoproterenol (Srivastava et al 2007), mice subjected to trans aortic constriction (Zhang et al 2007), heart failure (Liu et al 2005), rabbits subjected to myocardial infarction-induced heart failure (Qin et al 2007) and dogs subjected to tachycardia-induced heart failure (Zhang et al 2009). Lipid peroxidation products such as HNE are metabolically removed by several enzymes including aldose reductase (AR) (Baba et al 2018; Srivastava et al 1999; Srivastava et al 1998), aldehyde dehydrogenase (ALDH2) (Chen et al 2008; Gomes et al 2014) and glutathione-S-transferases (GSTs) (Conklin et al 2015).…”
Section: Introductionmentioning
confidence: 99%